Metabolic syndrome, lifestyle risk factors, and distal colon adenoma: A retrospective cohort study - Kim, Moon-Chan (Baishideng Publishing Group Co., Limited, 2011)
AIM: To investigate relationships between colorectal adenoma incidence, metabolic syndrome (MS) components and lifestyle factors. METHODS: We conducted a retrospective cohort study using data from individuals who had multiple sigmoidoscopies for colon cancer at the Health Promotion Center of Ulsan University Hospital in Korea from 1998 to 2007. RESULTS: By multivariate analysis, the incidence of distal colon adenoma was increased by more than 1.76 times in individuals with at least one component of MS compared to those without a component of MS. After adjustment for age, gender, smoking, drinking, and physical exercise, only high body mass index (BMI) was significantly associated with the incidence of distal colon adenoma (Hazard ratio 1.66, 95% confidence interval 1.05-2.62). CONCLUSION: Our results suggest that high BMI may increase the risk of colorectal adenoma in Korean adults.